Rat liver preproalbumin: in vitro synthesis and partial amino acid sequence. - Strauss, A W (1977)
Rat liver poly(A)-containing RNA greatly stimulated incorporation of radioactive amino acids into protein when added to a wheat germ in vitro translation system. Approximately 7% of the labeled synthetic product was precipitated following indirect immunoprecipitation with antisera to rat serum albumin. Analysis of this material, and of the cyanogen bromide fragments derived from it, by sodium dodecyl sulfate/polyacrylamide gel electrophoresis revealed that it contained an NH2-terminal extension of about 2500 daltons when compared to rat serum albumin. Automated sequence determination of purified cell-free product labeled with various radioactive amino acids revealed the presence of 18 additional amino acids NH2-terminal to the sequence of rat proalbumin. The partial sequence of this extension was found to be: Met-X-X-X-X-Phe-Leu-Leu-Leu-Leu-Phe-X-X-X-X-X-Phe-X-proalbumin. On the basis of this evidence, the immunoprecipitable cell-free product was designated preproalbumin.